2018
DOI: 10.11648/j.mlr.20180303.11
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on Leg Bone Fracture Detection and Classification Using X-ray Images

Abstract: Nowadays, computer aided diagnosis (CAD) system become popular because it improves the interpretation of the medical images compared to the early diagnosis of the various diseases for the doctors and the medical expert specialists. Similarly, bone fracture is a common problem due to pressure, accident and osteoporosis. Moreover, bone is rigid portion and supports the whole body. Therefore, the bone fracture is taken account of the important problem in recent year. Bone fracture detection using computer vision … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…However, the system produces the output results with accurate and reliable performance and less processing time based on the contributed methods. According to the result, best accuracy achieved was 83 % using the Kappa accuracy assessment [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the system produces the output results with accurate and reliable performance and less processing time based on the contributed methods. According to the result, best accuracy achieved was 83 % using the Kappa accuracy assessment [8].…”
Section: Introductionmentioning
confidence: 99%
“…In Myint et al (2018) work [8], suggested a Computer-Aided Diagnosis (CAD) technique to automatically recognize and localize the leg bone fracture. Many image processing techniques were used in their paper, they recognized that Harris corner detection was an effective tool to catch the broken points of the leg bone.…”
Section: Introductionmentioning
confidence: 99%
“…Before DCNN became available, conventional machine learning for fracture classi cation in medical images required image pre-processing and feature extraction [10]- [11] before proceeding to the classi cation procedure. Edge detection had to be conducted rst during image pre-processing, such as through a Harris corner detection [11], Gaussian edge detection, or Sobel edge detection [12]. Further extraction of "useful features" that machine learning can learn from is the key step in conventional machine learning.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, Gray Level Concurrency Matrix (GLCM) features was used in analysis of cancer cells using laser pico-projections images [33] or in detection of bone fractures in X-ray images [34]. Similarly, deep learning with CNN [35], application of K-Nearest Neighbors algorithm (KNN) to decision trees [36] have been applied for the analysis of X-ray image in order to detect and characterize bone fractures. Similar approaches have also been tested in ultrasonic echography.…”
Section: Introductionmentioning
confidence: 99%